Prenatal sonographic diagnosis of diastrophic dwarfism - Tongsong T. (2014)
A healthy 27-year-old pregnant woman underwent sonographic examination because her uterine size was large for 20 weeks' menstrual age. Sonograms showed short fetal limbs with hitchhiker thumbs and toes, thoracic scoliosis, clubbed feet, and polyhydramnios. The ossification of all bony structures appeared normal, and there was no evidence of fractures. On the basis of these sonographic findings, we diagnosed skeletal dysplasia and short-limbed dwarfism, most likely diastrophic dwarfism. We counseled the parents, and the pregnancy was continued. At 37 weeks menstrual age, the patient vaginally delivered a male infant that weighed 2,560 g. The infant survived with respiratory support during his first few days of life. Postnatal physical and radiologic examinations confirmed the prenatal diagnosis of diastrophic dwarfism. Sonography is the modality of choice for prenatal detection of diastrophic dwarfism. © 2002 John Wiley & Sons, Inc.